Utilizing waste manhole covers and fibreboard as reinforcing fillers for thermoplastic composites - Ayrilmis, Nadir; Kanat, Gurdal; Avsar, Esra Yildiz; Palanisamy, Sivasubramanian; Ashori, Alireza (SAGE PUBLICATIONS LTD, 2025)
This study investigated the potential of using recycled manhole cover flour (CMC) and medium density fibreboard (MDF) sawdust as low cost fillers for recycled polypropylene (PP) composites. Various compositions of CMC and MDF flour, up to 40 wt% (20 wt% CMC and 20 wt% MDF), were compounded with recycled PP using maleic anhydride grafted PP. The results showed that increasing the filler content improved the bending strength and modulus, reaching 46.4 MPa and 3399 MPa, respectively, at 40 wt% loading. However, the tensile strength decreased slightly with the addition of 10 wt% filler and showed a slight decrease with the increase in filler content from 20 to 40 wt%. The water absorption of the composites showed only a slight increase from 0% for pure PP to 0.007% for composites with 40 wt% filler. Thermogravimetric analysis confirmed the thermal stability of the composites up to about 400 degrees C. This study demonstrated the potential of using a blend of waste CMC and MDF flour up to 40 wt% to improve the strength and water resistance of recycled PP composites, offering a promising and sustainable approach to cost-effective composite production.
Keywords: Interfacial adhesion; manhole cover; medium density fibreboard sawdust; recycled polypropylene; reinforcing filler; thermoplastic composites; WOOD-PLASTIC COMPOSITES; MECHANICAL-PROPERTIES; POLYPROPYLENE COMPOSITES; CHEMICAL TREATMENTS; STRENGTH; FIBERS; TALC; Materials Science; Polymer Science